RELATIONSHIP BETWEEN NURSING TEAMWORK AND MISSED NURSING CARE IN INTENSIVE CARE UNITS - Onny Ega Isfadillah; Retno Purwandari; Kholid Rosyidi Muhammad Nur; Nurfika Asmaningrum; Yulia Kurniawati (Universitas Muhammadiyah Ponorogo, 2026)
Nurses play a vital role in providing nursing care, especially in intensive care units. Low levels of nursing teamwork can contribute to the occurrence of missed nursing care, which refers to nursing actions that are delayed or not performed. Given that patients in intensive care units require comprehensive and continuous care, optimal nursing teamwork is essential to ensure the quality of patient care. This research aimed to determine the relationship between the level of nursing teamwork and the incidence of missed nursing care in patient care in the intensive care units of dr. Soebandi General Hospital, Jember. Method: This research was non-experimental quantitative study with a correlational design and a cross-sectional approach. The study sample consisted of 72 active nurses who worked in the intensive care units of RSD dr. Soebandi Jember. Data analysis was conducted using the Spearman Rank correlation test. Results: The results of the analysis showed a moderate level of teamwork and low missed nursing care with a significant negative correlation between the level of nursing teamwork and the incidence of missed nursing care, with a p value <0.05 (0.000 <0.05) and a correlation coefficient of -0.404. Conclusion: The bivariate analysis showed that there was a significant relationship between teamwork and missed nursing care. Hospitals need to support nurse training programs, particularly in enhancing teamwork skills.